2015
DOI: 10.1002/hyp.10442
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation input and antecedent soil moisture effects on mercury mobility in soil—laboratory experiments with an enriched stable isotope tracer

Abstract: Terrestrial soils are net mercury (Hg) sinks, but leaching of Hg from upland environments constitutes an important source to downstream wetlands and water bodies. Broadly, hydrology is instrumental in facilitating Hg transport within, and export from watersheds but the relative influences of specific hydrological factors such as antecedent soil moisture and precipitation in controlling the transport of Hg through upland soils are not well understood. The purpose of this research was to elucidate the relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The observed behavior of the stream water Hg D :DOC ratio scaling with SOC content can be further explored by considering soil‐level processes. For individual watersheds, models might account for spatial heterogeneity (both vertical and horizontal) in soil Hg and carbon pools [ Demers et al ., ; Burns et al ., ] and/or depict transport along distinct flow pathways under variable hydrological conditions [ Demers et al ., ; Oswald and Branfireun , ; Haynes and Mitchell , ]. Modeling the coupled transport of Hg D and DOC across a diverse array of watersheds necessarily requires simplifications, with a focus on first‐order processes and bulk properties of the watersheds.…”
Section: A Mathematical Framework For Interpretation Of Resultsmentioning
confidence: 99%
“…The observed behavior of the stream water Hg D :DOC ratio scaling with SOC content can be further explored by considering soil‐level processes. For individual watersheds, models might account for spatial heterogeneity (both vertical and horizontal) in soil Hg and carbon pools [ Demers et al ., ; Burns et al ., ] and/or depict transport along distinct flow pathways under variable hydrological conditions [ Demers et al ., ; Oswald and Branfireun , ; Haynes and Mitchell , ]. Modeling the coupled transport of Hg D and DOC across a diverse array of watersheds necessarily requires simplifications, with a focus on first‐order processes and bulk properties of the watersheds.…”
Section: A Mathematical Framework For Interpretation Of Resultsmentioning
confidence: 99%
“…Contrary to Cd, Hg was not detected in leachate, while the distribution ratio in surface residues was significantly higher than the other seven elements. Studies have shown that the majority of the added Hg tended to be bound by soil organic matter on the surface and precipitation input had a slight influence on its mobility [52][53][54]. This may explain the large distribution ratio of Hg in surface residues and the reason for its obvious growth with the increased adding of sludge.…”
Section: Discussionmentioning
confidence: 99%